2012
DOI: 10.1111/j.1365-2850.2012.01954.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of heavy episodic drinking among Korean adolescents

Abstract: The main objective of this study was to identify the risk factors and develop a decision tree model of heavy episodic drinking (HED) among adolescents. Data were obtained from a representative nationwide Korean population. Nine variables (such as last 30 days smoking, school grade, sex, depression, school achievement, level of stress, region, and economic status) were found as risk factors of HED. On the highest level of the tree root, major classification rule was played by dividing based on the last 30 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
8
7
0
Order By: Relevance
“…Asian adolescents in BC and in South Korea shared seven factors associated with heavy drinking: six risk factors and one protective factor. Smoking cigarettes was the strongest risk factor, which is consistent with previous studies of adolescents in South Korea (Chung & Joung, 2013) and US (Chung & Joung, 2018) which showed cigarette use as the main predictor of heavy drinking. Similarly, a study from Ontario, Canada showed a significant overlap in cigarette smoking and heavy drinking (Larsen et al, 2017).…”
Section: Shared Risk and Protective Factors For Heavy Drinking Amonsupporting
confidence: 91%
See 1 more Smart Citation
“…Asian adolescents in BC and in South Korea shared seven factors associated with heavy drinking: six risk factors and one protective factor. Smoking cigarettes was the strongest risk factor, which is consistent with previous studies of adolescents in South Korea (Chung & Joung, 2013) and US (Chung & Joung, 2018) which showed cigarette use as the main predictor of heavy drinking. Similarly, a study from Ontario, Canada showed a significant overlap in cigarette smoking and heavy drinking (Larsen et al, 2017).…”
Section: Shared Risk and Protective Factors For Heavy Drinking Amonsupporting
confidence: 91%
“…Previous studies exploring predictors related to heavy drinking among adolescents in various countries have identified a number of predictors, including differences by gender (Iwamoto et al, 2016), school grade (Chung & Joung, 2013;Larsen et al, 2017), bullying victimization (Wang et al, 2018), depression (Lamis, Ballard, May, & Dvorak, 2016), sleep quality (Hasler et al, 2017), exercise (Chung & Joung, 2018), current cigarette smoking (Chung & Joung, 2013), and sexual experience (Wang et al, 2018). Although these demographic characteristics and health and risk behaviors are often related or co-occurring, most of the preceding studies have studied only one concept, or have been studied only in the adolescents of one country (Chung & Joung, 2013), or have been conducted in other countries, such as US (Chung & Joung, 2018;Iwamoto et al, 2016). Considering the high likelihood for heavy drinking among Asian adolescents who experience acculturation stress (Iwamoto et al, 2016), further attention is needed to these patterns for BC Asian adolescents and South Korean adolescents.…”
Section: Introductionmentioning
confidence: 99%
“… 15 The higher prevalence among boys than girls was consistent with results from other studies, 15 18 34 but differs from a Korean study, in which no sex difference was observed. 14 The highest prevalence of binge drinking in the current study was among students attending vocational high schools. A possible explanation for this was that, compared with middle school and academic high school students, vocational high school students are likely to enter employment immediately following graduation, for which social communication and interaction, possibly associated with alcohol consumption, may be considered important.…”
Section: Discussionmentioning
confidence: 57%
“…12 In the USA, the prevalence declined from 31.3% in 1991 to 17.7% in 2015. 13 In Asia, the prevalence of heavy episodic drinking (ie, binge drinking) among grade 7–12 students was 10.3% in Korea, 14 while 21.2% of students, with mean age 14.7 years, reported drinking alcohol in the past 30 days and 7.1% reported binge drinking in Hong Kong. 15 In mainland China, a study of 7344 middle school students conducted in four cities (Beijing, Hangzhou, Wuhan, Urumchi) found that the prevalence of current drinking was 14.4%, and 9.9% of students had experienced drunkenness, with significant regional differences.…”
Section: Introductionmentioning
confidence: 99%
“…The age distributions of these undergraduate college students is approximately <21 years (45.5%), 21 to 23 years (48.1%), and ≥24 years (28.5%), respectively. According to 2009 Korea national data, excessive alcohol consumption in a single session or day was reported by 10.3% of respondent students in grades 7 to 12 [ 4 ]. Young adults and adolescents who are at risk for early diabetes and prediabetes also tend to be exposed to excessive or binge drinking.…”
Section: Introductionmentioning
confidence: 99%